Islamic Education and Economics: The Foundation of Hadith-Based Ethics in Islamic Educational Thought - Siti Nur Qamariyah; Mohammad Fattah (Penerbit Hellow Pustaka, 2026)
Islamic education plays a strategic role in shaping ethical economic behavior through the internalization of Islamic values. One of the primary sources of Islamic economic ethics is the hadith of the Prophet Muhammad (peace be upon him), which contains moral principles governing economic activities, such as honesty, trustworthiness, justice, balance, and social responsibility. This study aims to analyze hadith-based economic ethics within Islamic educational thought and to examine its relevance in fostering just and sustainable economic behavior. This research employs a qualitative approach using library research methods. Data were collected from the hadiths of the Prophet Muhammad, classical and contemporary hadith commentaries, as well as reputable international journal articles related to Islamic education and Islamic economics. Data analysis was conducted through content analysis using a thematic approach. The findings indicate that the hadith of the Prophet Muhammad encompasses comprehensive and contextual economic ethical values that can serve as a foundational framework for Islamic educational thought. These values are not only normative but also practical in shaping students’ economic character. Islamic education plays a crucial role in internalizing hadith-based economic ethics through integrative and contextual learning processes. This study concludes that strengthening Islamic education grounded in hadith-based economic ethics contributes to the development of individuals who are not only economically competent but also possess strong moral integrity and social responsibility.